Moral competencies of future Muslim accountants in Malaysia - Zubairu, Umaru Mustapha (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2017)
The moral credibility of the accounting profession has been left in disarray over the last two decades due to a rash of accounting scandals over that period. In a bid to restore the integrity of the profession, universities have been suggested as key stakeholders to produce morally competent future accountants. The Malaysian government has subscribed to this notion, as evidenced by its recent policy initiatives that task Malaysian universities to emphasise the moral development of their students. It is against this backdrop that this study sought to evaluate the impact of the ethical climate of Islamic universities in Malaysia on the moral competencies of the country's future Muslim accountants. The study had five objectives: 1) to develop a profile of a morally competent Muslim accountant, 2) to develop an instrument that would measure the ethical principles that make up the profile of a morally competent Muslim accountant, 3) to compare between the moral competencies of second-year and fourth-year Muslim accounting students, 4) to compare between the moral competencies of fourth-year Muslim accounting students enrolled in Islamic universities and the moral competencies of the fourth-year Muslim accounting students enrolled in conventional universities and 5) to identify and assess the strengths and weaknesses in the moral competencies of Muslim accounting students enrolled in Islamic universities. Specifically, the International Islamic University Malaysia (IIUM) and Universiti Sains Islam Malaysia (USIM) were selected as they were the only Islamic universities that have accounting programmes accredited by the Malaysian Institute of Accountants. Universiti Utara Malaysia (UUM) and Universiti Teknologi Mara (UiTM) were selected as control universities. An ethical scenario-based instrument titled the Muslim Accountant Moral Competency Test (MAMOC) was developed with the collaboration of five Islamic accounting scholars to measure the moral competencies of second-year and fourth-year accounting students in the selected universities. MAMOC was completed by a total of 764 students (IIUM – 125 second-year and 72 final-year; USIM – 67 second-year and 88 final-year; UUM – 133 second-year and 101 final-year; UiTM – 83 second-year and 95 final-year). T-tests were used to compare the moral competencies of second-year Islamic university students and fourth-year students; there was no significant difference in the moral competencies of these two groups after controlling for religiosity. T-tests were also used to compare the moral competencies of fourth-year students from Islamic universities and conventional universities; the results showed that Islamic-university fourth-year Muslim accounting students had significantly higher moral competencies than their conventional university counterparts. Although the results revealed that the ethical climate of Islamic universities had a greater impact on the moral competencies of Muslim accounting students as compared to the impact of conventional universities, an overall assessment of the moral competencies of the students revealed that there is significant room for improvement, particularly in the area of selecting Islamically-appropriate jobs and avoiding dealing with interest. There is thus a crucial need for Islamic universities in Malaysia to review the ethical content of their curricula in order to address the weaknesses in moral competencies of Muslim accounting students that were revealed in this study.